Quercetin alleviates chronic renal failure by targeting the PI3k/Akt pathway. Issue 1 (1st January 2021) - Tu, Haitao; Ma, Duanhua; Luo, Yuanyuan; Tang, Shuifu; Li, Ying; Chen, Gangyi; Wang, Liangliang; Hou, Zhengkun; Shen, Chuangpeng; Lu, Huan; Zhuang, Xun; Zhang, Liangyou
ABSTRACT: Chronic renal failure (CRF) threatens human health greatly and attracts worldwide concerns of health professionals in the public health sector. In our preliminary study, we found that Compound capsule (Shengqing Jiangzhuo Capsule, SQJZJN) had a significant therapeutic effect on CRF. Quercetin is one of the main components of this Compound capsule. In this study, we investigated the effect of Quercetin monomer on CRF and the regulation of PI3k/Akt pathway. Network pharmacology analysis methods were employed to analyze the SQJZJN/Quercetin/PIK3R1 network relationships. In this study, a CRF rat model was prepared using the gavage adenine solution method and detected the indicators of Creatinine (Cr), Blood Urea Nitrogen (BUN), and Uric Acid (UA). After treating the rat model with Quercetin and PIK3R1-interfering lentivirus, respectively, we observed the changes on the histological morphology of the kidney and detected apoptosis using TUNEL staining. Gene and protein expression associated with renal function were detected using qPCR, WB and immunofluorescence. Quercetin was identified as the main ingredient of SQJZJN by the network pharmacological screening and Quercetin at 1.5 and 3 g/(kg.d) concentrations could effectively alleviate the CRF symptoms, reduce the levels of Cr, BUN, and UA, and markedly inhibit cell apoptosis demonstrated by the intragastric administration. Furthermore, the protein expression of p-PI3K, p-AKT, NLRP3, caspase1, AQP1, and AQP2 in all groups was detected by immunofluorescence and western blot assays, indicating that Quercetin could reduce the expression of NLRP3, caspase1, p-PI3k, and p-Akt, and increase the expression of AQP1 and AQP2 in the renal tissues of CRF rats. Being labeled with biotin and incubated with the total protein extracted from kidney tissues, Quercetin could bind to PIK3R1. Following the PIK3R1 interference lentivirus was injected into the CRF model rats by tail vein, the CRF symptoms were effectively alleviated in the PIK3R1 interference group, consistent with the effect of Quercetin. Taken together, Quercetin, a major component of SQJZJN, might minimize renal fibrosis and apoptosis in CRF rats by inhibiting the PI3k/Akt pathway through targeting PIK3R1. By regulating AQP1 and AQP2, both water retention and toxin accumulation were reduced. ABSTRACT: uf0001